2014
DOI: 10.1155/2014/384783
|View full text |Cite
|
Sign up to set email alerts
|

Tackling Negative Symptoms of Schizophrenia with Memantine

Abstract: We present a case of a 52-year-old male patient suffering from chronic schizophrenia stabilized on risperidone long-acting injection (37,5 mg/2 weeks) and biperiden 4 mg/day. Residual symptoms are affective flattening, alogia, avolition, and asociality. Memantine 10 mg/day was added. After 1.5 months, the patient spontaneously referred to “feel better being in company of my relatives.” The following scales have been completed: the Scale for the Assessment of Negative Symptoms (96), the Scale for the Assessment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 17 publications
(18 reference statements)
0
16
0
Order By: Relevance
“…In an RCT with 28 chronic poststroke patients, memantine was effective for aphasia [123]. In a 52-year-old man with schizophrenia, memantine 20 mg daily for 2 months decreased SANS scores from 96 to 70 (avolition-apathy: −8, anhedonia-asociality: −7, affective flattening: −7, alogia: −1, and attention: −3) in 4 months [124]. Participants with deficit schizophrenia ( n = 40) showed increased IgA responses to KP metabolites such as xanthurenic acid, picolinic acid, and quinolinic acid and relatively lowered IgA responses to KYNA and anthranilic acid compared to healthy controls ( n = 40) and 40 subjects with nondeficit schizophrenia [125].…”
Section: Negative Symptomsmentioning
confidence: 99%
“…In an RCT with 28 chronic poststroke patients, memantine was effective for aphasia [123]. In a 52-year-old man with schizophrenia, memantine 20 mg daily for 2 months decreased SANS scores from 96 to 70 (avolition-apathy: −8, anhedonia-asociality: −7, affective flattening: −7, alogia: −1, and attention: −3) in 4 months [124]. Participants with deficit schizophrenia ( n = 40) showed increased IgA responses to KP metabolites such as xanthurenic acid, picolinic acid, and quinolinic acid and relatively lowered IgA responses to KYNA and anthranilic acid compared to healthy controls ( n = 40) and 40 subjects with nondeficit schizophrenia [125].…”
Section: Negative Symptomsmentioning
confidence: 99%
“…A chart-based retrospective case series found improved positive and/or negative symptoms as well as cognitive and/or functional domains in 17 out of 26 SZ patients when MEM was added to an antipsychotic (John et al, 2014); in several patients, antipsychotic dose requirements also declined with MEM. Many case reports describe symptom reduction and function gains after MEM (5-20 mg/d) in SZ patients; in some, symptoms returned when MEM was stopped and resolved after MEM was restarted (Zdanys and Tampi, 2008;Matsuda et al, 2013;Paraschakis, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…However, a recent case report indicated that another NMDAR antagonist, memantine significantly improved the negative symptoms of schizophrenia when used as add-on therapy. 276 Adjunctive memantine together with clozapine also significantly improved not only the negative symptoms but also positive symptoms in refractory schizophrenia patients. 277 The authors argue that this improvement could be related to memantine's NMDAR antagonistic mechanisms; preventing a toxic influx of Ca 2+ into neuronal cells and as such abrogating oxidative stress (see fig.…”
Section: Compounds Targeting Immune-inflammatory Responsesmentioning
confidence: 98%